A comparative analysis of the proximate and mineral composition of whole Citrus limon and Citrus clementina as a prospective alternative feed resource for livestock farming in South Africa - Idamokoro, Emrobowansan Monday; Hosu, Yiseyon Sunday; Oyedeji, Opeoluwa Oyehan; Miya, Gugulethu Mathews; Kuria, Simon Kamande; Oyedeji, Adebola Omowunmi (Frontiers in Sustainable Food Systems, 2022)
Citrus is a well-known vital fruit grown in South Africa. The presence of important bio-nutrients and metabolites within the different Citrus fruits indicate its significant nutritional qualities. This study is aimed to evaluate the proximate and mineral components of whole Citrus limon and Citrus clementina while considering them as prospective feed material for livestock farmers in South Africa. The nutritional evaluation was done using standard analytical procedures of the Association of Official Analytical Chemists (AOAC). The mineral constituents of the whole citrus samples were analysed using the inductively coupled plasma optical emission spectroscopy (ICP-OES). From the result, the nutritional analysis showed that the whole Citrus limon contains significantly higher moisture content (14.13±0.57) and fibre content (24.48±0.61) than Citrus clementina (11.41±1.24 and 20.66±1.07). Meanwhile Citrus clementina had a significantly higher protein value (8.65±0.04) compared to Citrus limon (5.53±0.10). Furthermore, the whole Citrus clementina had significantly higher K, Na, P, Zn, and Na+/K+ (1513.33±16.99, 53.33±4.71, 160.00±0.00, 4.80±0.00 and 1.09±0.01) than whole Citrus limon (1356.67±20.55, 30.00±0.00, 133.33±4.71,1.67±0.09 and 0.80±0.02), respectively. While Citrus limon had significantly higher Ca, Mg, Mn and Fe (593.33±4.71, 160.00±0.00, 1.00±0.00 and 4.53±0.25) compared to Citrus clementina (483.33±4.71, 136.67±4.71, 0.80±1.11 and 3.43±0.05). The study revealed variations in some nutritional and mineral components of whole Citrus limon and Citrus clementina, however, both citrus fruits have the potential to be explored to more significant livestock nutritional use in South Africa.